Thermo-enhanced upconversion luminescence in inert-core/active-shell UCNPs: the inert core matters. Issue 13 (6th April 2021) - Zhou, Youhui; Cheng, Yao; Xu, Ju; Lin, Hang; Wang, Yuansheng
Abstract : The thermal alleviation of surface quenching associated with size-dependent thermal expansion coefficient gives rise to the core-size-dependent abnormal luminescence thermal behavior in the inert-core/active-shell upconversion nanoparticles. Abstract : Recent discoveries regarding the anomalous thermo-enhanced luminescence of upconversion nanoparticles (UCNPs) have attracted great interest because of their potentially significant technological importance. Meanwhile, the great debate about the underlying mechanism responsible for this unique luminescence thermal behavior may be equally compelling. To this point, special attention has been paid to the critical interplay between surface species and the energy transfer process (from the sensitizer to the activator) in a thermal field. Herein, inert-core/active-shell UCNPs, in which both the sensitizer and activator are located in the shell area near the nanoparticle surface, have been designed to achieve temperature-dependent upconversion luminescence (UCL) behavior. The results show that the inert-core/active-shell UCNPs exhibit a stronger luminescence thermal enhancement tendency compared to the active-core UCNPs. Specifically, the luminescence thermal enhancement behavior of the inert-core/active-shell UCNPs appears to be core-size dependent, which cannot be explained by either a surface-phonon-assisted mechanism or a surface moisture release mechanism. Based on the relationship between the size-dependent luminescence and size-dependent lattice expansion coefficient, we suggest that the alleviation of the surface quenching induced by lattice thermal expansion is responsible for the presented luminescence thermal behavior of the inert-core/active-shell UCNPs.